MULTIMODE CASCADE INVERTER MODEL DESIGNED FOR REACTIVE POWER COMPENSATION AND DISTORTION POWER IN GRIDS WITH RECTIFIER LOAD NATURE - Loskutov А.B.; Altunin B.Iu.; Karnavsky I.А. (Problems of the Regional Energetics, 2011)
This article presents trends of development and research in the region of increase of the electric energy quality and electromagnetic compatibility of middle big power load with rectifier type. It is developed the simulation model of compensator unit. There are presented results of simulation of the inactive power compensator which is based on the multimode cascade inverter.